Effect of reinforcement bending on the elastic properties of interpenetrating phase composites. (September 2019) - Seetoh, Ian; Markandan, Kalaimani; Lai, Chang Quan
Highlights: Developed a model that takes reinforcement bending into account for the prediction of the elastic modulus of interpenetrating phase composite (IPC). A dimensionless parameter was introduced for determining if reinforcement bending is significant in the deformation of an IPC. The model is applicable over a wide range of reinforcement volume fraction, matrix and reinforcement moduli and reinforcement design. The model was validated with experimental results, including those previously published by other groups, as well as with finite element simulations. The current model is shown to be more accurate than other models, particularly at low matrix modulus and reinforcement volume fraction. Abstract: The elastic modulus of interpenetrating phase composites (IPCs) was analyzed through a theoretical model that accounted for bending deformation of the reinforcement phase. The model was validated against literature data, as well as simulation and experimental results of IPCs that were constructed from 3D-printed polymeric reinforcements embedded in a polydimethylsiloxane (PDMS) matrix. The reinforcements were in the form of Octet Truss and Kelvin Cell lattices, which are known to exhibit very different degrees of bending during elastic deformation. When the matrix modulus was relatively low, the model was able to explain how the bending of reinforcement struts caused the overall IPC modulus to be much lower than those predicted by other theoretical models. As the matrix modulus increased to beyond 20% that of the reinforcement material, however, the different lattice designs were found to have no significant influence on the IPC modulus. Further increase in matrix modulus pushed the elastic response of IPCs towards the isostrain limit, as the matrix helped to distribute the load more evenly and suppress the bending of struts, especially for lower density lattices. The model was able to account for a wide range of different constituent moduli and was also applicable to IPCs which utilized stochastic foams for reinforcement. The insights derived in this study is expected to be particularly useful for designing polymer-based IPCs where the elastic moduli of the reinforcement and matrix can differ over several orders of magnitude.